Absence of evidence for the effectiveness of five interventions routinely used in the intensive care management of severe head injury: a systematic review. Issue 5 (1st November 1998) - Roberts, Ian; Schierhout, Gillian; Alderson, Phil
Abstract : OBJECTIVES: To assess the effectiveness of interventions routinely used in the intensive care management of severe head injury, specifically, the effectiveness of hyperventilation, mannitol, CSF drainage, barbiturates, and corticosteroids. METHODS: Systematic review of all unconfounded randomised trials, published or unpublished, that were available by August 1996. RESULTS: None of the interventions has been reliably shown to reduce death or disability after severe head injury. One trial of hyperventilation was identified of 77 participants. The relative risk for death was 0.73 (95% confidence interval (95% CI) 0.36–1.49), and for death or disability it was 1.14 (95% CI 0.82–1.58). One trial of mannitol was identified of 41 participants. The relative risk for death was 1.75 (95% CI 0.48–6.38), no data were available for disability. No randomised trials of CSF drainage were identified. Two randomised trials of barbiturate therapy were identified, including 126 participants. The pooled relative risk for death was 1.12 (95% CI 0.81–1.54). Disability data were available for one trial. The relative risk for death or disability was 0.96 (95% CI 0.62–1.49). Thirteen randomised trials of corticosteroids were identified, comprising 2073 participants. The pooled relative risk for death was 0.95 (0.84 to 1.07) and for death or disability it was 1.01 (95% CI 0.91 to 1.11). On the basis of the currently available randomised evidence, for every intervention studied it is impossible to refute either a moderate increase or a moderate decrease in the risk of death or disability. CONCLUSION: Existing trials have been too small to support or refute the existence of a real benefit from using hyperventilation, mannitol, CSF drainage, barbiturates, or corticosteroids. Further large scale randomised trials of these interventions are required.